Risk factors and screening benefits in pregestational and early gestation diabetes - Dahab, Amaal Abdo; Aljohani, Taghreed Mohamed; Heameed, Roaa Ali; Alshehri, Faisal Abdullah; Alrasheedi, Maha Zaidan; Alsaegh, Amna Ismaeel; Yahya, Safa Metahr; Alanazi, Deema Faleh; Alsomali, Abdullah Jama; Zainaldeen, Amani Mohammed Al; Slais, Zainab Adel (International Journal Of Community Medicine And Public Health, 2022)
Gestational diabetes is one of the most widespread complications of pregnancy posing a serious clinical and public health challenge. Globally, 16.5% of pregnancies are affected by the gestational diabetes, and this percentage is expected to rise as the obesity pandemic spreads. It has severe short-term and long-term negative health effects on both the mother and the child, which emphasizes the importance of identifying the risk factors for gestational diabetes and taking steps to prevent the illness. Gestational diabetes occurs when pregnant women who have never been diagnosed with diabetes experience chronic hyperglycaemia caused by impaired glucose tolerance. Obesity, physical inactivity, multiparity, family history of diabetes mellitus, certain ethnicities, birth of a previous macrocosmic child are all risk factors for gestational diabetes. Maternal cardiovascular disease, type 2 diabetes, macrosomia, and difficulties in delivery are all some of the complications of gestational diabetes. Additionally, there is a longer-term risk for the child to develop obesity, type 2 diabetes, and cardiovascular disease. Screening and diagnostic tests for gestational diabetes are essential to identify the women who are at risk for developing gestational diabetes and thereafter reduce or eliminate the risk of unfavourable outcomes for both mother and child associated with gestational diabetes. Oral glucose tolerance test is the widely accepted screening test conducted between 24-28 weeks of pregnancy for the diagnosis of gestational diabetes. The purpose of this research is to review the available information about risk factors and screening benefits in pregestational and early gestational diabetes.